Gambaran Kadar Asam Urat pada Lansia - Rizki Kurniawan; Kartinah Kartinah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe uric acid levels in older people in Pucangan Village, Kartusara District. The method used in this research is a quantitative method using a descriptive approach. The results obtained from this study were an examination of uric acid levels showing that normal uric acid levels had the highest frequency of 60.4%. In comparison, high uric acid levels were as much as 39.6%. In conclusion, older people in the Posyandu of Pucangan Village gender dominated this study, namely women; the majority of the ages from the study's results were the age range of 60-65 years, and the most educational level status was elementary school. With the results, uric acid levels are still expected, and women most experience high uric acid levels. Keywords: Uric Acid, Elderly